Serum Growth Hormone Levels and the Response of Diabetic Retinopathy to Pituitary Ablation - Wright, A. D. (1969)
Serum growth hormone levels were measured during insulin tolerance tests in 36 patients after yttrium-90 pituitary implantation for diabetic retinopathy. The response of the new blood vessels was more clearly related to loss of growth hormone function than was the improvement of retinal haemorrhages and microaneurysms. The overall response of the retinopathy was greatest when growth hormone function was lost. Since the loss of growth hormone function was related to the loss of other aspects of anterior pituitary function, a unique role of growth hormone in the response of diabetic retinopathy to pituitary ablation could not be established.